AKTUALISASI PROGRAM KERJA “RUMAH” KREATIFITAS MAHASISWA MELALUI KEGIATAN RIHLAH DAKWAH - irwandi irwandi; Romi Maimori (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The implementation of the Rihla Dakwah activity is an annual program carried out by the students of Faukulta Ushuluddin, Adab and Da'wah of IAIN Batusangkar which is facilitated by the student's creative